EFFECT OF EDUCATION ON HEALTH BEHAVIOR IN ADULT HYPERTENSION PREVENTION OF AGE 20-45 YEARS (In Hamlet Talaga village Talaga District of Nonggunong East Java Province Sumenep) - . Abdurrohman; Endang Yuswatiningsih; Dwi Prasetyaningati (Jurnal Keperawatan, 2014)
Hypertension is a global problem because of its prevalence continues to increase in line with the behavioral changes that include unhealthy habits such as lifestyle changes, excessive eating habits, too much activity, smoking, and lack of rest. The purpose of this study is to analyze Effect of health education on hypertension prevention behaviors in adulthood aged 20-45 years In Hamlet Talaga village Talaga District of Nonggunong East Java Province Sumenep. The design used in this study was pre-experimental methods One Group Pre-test post-test design with a community population of all adults aged 20-45 years in the hamlet Subdistrict Talaga Talaga village Nonggunong Sumenep totaling 156 people and 31 with a sample of stratified proportional random sampling. This study consisted of two variables: the dependent variable and the independent variables of health education behavioral prevention of hypertension in adult community aged 20-45 years, while collecting data using questionnaires. And the statistical test using the paired t-test. The results of the pretest showed a small community of adult age aged 20-45 years (19.35%) or 6 respondents have good behavior, the majority (51.61%) or 16 respondents, and (29.03%) or 9 respondents have behavioral less, while the posttest results obtained majority (70.97%) or 22 of the respondents have good behavior, as many (16.13%) or 5 respondents have behavioral being, and (12.9%) or 4 respondents have less behavior. The results of the statistical test paired T-test (p = 0.001 <α = 0.05) so H1 accepted. Based on the results of this study concluded that there is influence of Behavioral Health Education on Prevention of Hypertension in adulthood community aged 20-45 years of behavior is becoming a good behavior.Keywords: Health education, behavior, hypertension.